An intercultural theology of migration : pilgrims in the wilderness - Cruz, Gemma Tulud, 1970- (Studies in Systematic Theology, 2010)
Migration has long been associated with the social sciences. However, as a phenomenon that provides windows into possibly new forms of oppression and, at the same time, paths toward human liberation a systematic theological look at contemporary migration is long overdue. Building on the emerging interest on migration in theology this book presents an intercultural theology of migration drawn from the experience of Filipino women domestic workers in Hong Kong in dialogue with theological ethics and liberationist theologies. The result is a new look at the phenomenon of contemporary migration.